Efficacy and harms of orally, intramuscularly or intravenously administered glucocorticoids for sciatica: A systematic review and meta‐analysis. (30th January 2020) - Abdel Shaheed, Christina; Maher, Chris G.; Buchbinder, Rachelle; Ng, Beverly; Enke, Oliver; Guzowski, Robert; McLachlan, Andrew J.; Day, Ric O.; Richards, Bethan; Latimer, Jane; Lin, Chung‐Wei Christine
Abstract: Background: Sciatica can be a debilitating condition and there is limited guidance on the use of glucocorticoids administered via the oral, intramuscular or intravenous route for this condition. These represent viable treatment options in the primary care setting. Objective: To evaluate the evidence on efficacy and harms of oral, IM and IV glucocorticoid administration for sciatica. Databases and data treatment: MEDLINE, EMBASE, CENTRAL, CINAHL, PsycINFO (inception to October 2018) were searched for randomised placebo‐controlled trials evaluating oral, IV or IM glucocorticoid administration for sciatica. Two authors extracted outcomes data. Continuous pain and disability outcomes were converted to a 0 (no pain/disability) to 100 (worst pain/disability) scale. Data were pooled using a random effects model. Overall quality of evidence was assessed using GRADE. Primary outcomes were leg pain and disability. Primary follow‐up period was the immediate‐term (<2 weeks from administration). We also considered adverse events. Results: Nine trials were eligible. One study [ n  = 27] provided low quality evidence of a small reduction in disability with early administration of oral prednisone (within 1 week); MD −13.4 [−23.3, −3.5] but not for pain MD −2.5 [−16.9, 11.9]. There was low quality evidence from one study [ n  = 78] of moderate reduction in disability and small reduction in pain with early (within 72 hr of symptom onset) single intramuscular administration of methylprednisolone acetate; MD −24.5 [−38.8, −10.2] and −14.0 [−27.4, −0.6], respectively. There were no immediate‐term benefits with IV administration. Conclusion: The effects of glucocorticoids on immediate‐term leg pain or disability are uncertain. Future large high quality trials are needed to resolve this uncertainty.